Klarspråk – demokratiprojekt, kvalitetsmätning eller ”småtips” i arbetet? - Palicki, Lena Lind (Klart språk i Norden, 2014)
The plain language work in Sweden is fundamentally a political language planning project. Plain language is well established nowadays, with an elaborate practice and traditions dating back to the 1950s. However, it still seems difficult to really pin down what plain language is. What is plain language at the policy level, and what does it become once it is put into practice? Words used when arguing for plain language include democracy, efficiency and the safeguarding of legal rights. But what happens when such a language policy project is to be implemented? When it becomes necessary to take into account local resources, aims and motives? Plain language is implemented in different ways and at several different levels. In my presentation I focus on plain language policy documents as well as the practical implementation: plain language education, and the plain language texts of commercial language advisory companies.